1968
DOI: 10.1039/j39680002070
|View full text |Cite
|
Sign up to set email alerts
|

Carcinogenic nitrogen compounds. Part LXI. The Skraup reaction with diamines derived from acenaphthene and anthracene

Abstract: Diaminoanthracene and 5.6-diaminoacenaphthene readily undergo double Skraup cyclisation to benzo[l,2h : 4.5-h'ldiquinoline and dipyrido[2,3-e : 2.3-hlacenaphthene. Under the same conditions. however, 3.6diaminoacenaphthene gave only a monocyclisation product, 3-aminoindeno[l,7-gh]quinoline, and 3.8-diaminoacenaphthene remained pratically unchanged ; this suggests bond fixation in the aromatic framework of these two diamines. N.m.r. spectra were used to ascertain structures of acenaphthene intermediates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

1970
1970
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
0
6
1
Order By: Relevance
“…3-Amino-1,2-dihydroindeno[1,7- gh ]quinoline ( 35 ) was prepared from 32 according to the literature procedure . It was then converted into its acetyl derivative 36 in quantitative yield by acetic anhydride in THF: mp 226−227 °C (after crystallization from methanol); 1 H NMR (CDCl 3 + DMSO- d 6 ) 2.22 (s, 3, CH 3 ), 3.39 (m, 4, CH 2 ), 7.45−7.50 (q, 1, H-8), 7.94−7.97 (d, 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…3-Amino-1,2-dihydroindeno[1,7- gh ]quinoline ( 35 ) was prepared from 32 according to the literature procedure . It was then converted into its acetyl derivative 36 in quantitative yield by acetic anhydride in THF: mp 226−227 °C (after crystallization from methanol); 1 H NMR (CDCl 3 + DMSO- d 6 ) 2.22 (s, 3, CH 3 ), 3.39 (m, 4, CH 2 ), 7.45−7.50 (q, 1, H-8), 7.94−7.97 (d, 1.…”
Section: Methodsmentioning
confidence: 99%
“…Four different azaphenanthrene analogues of azonafide ( 42 − 45 ), with nitrogen replacing CH at either the 8 or the 11 position, were prepared from aminoacenaphthenes as shown in Scheme . When the Skraup reaction was run on 5-aminoacenaphthene ( 30 ), the product was 1,2-dihydroindeno[1,7- gh ]quinoline 33 . Oxidation of 33 with potassium dichromate in acetic acid gave anhydride 39 directly, and treatment with N , N -dimethylethylenediamine in ethanol and toluene at reflux then afforded 8-azaphenanthrene derivative 42 (5-[2‘-(dimethylamino)ethyl]-5,6-dihydro-4 H -quinolino[6,7,8- de ]isoquinoline-4,6-dione).…”
Section: Chemistrymentioning
confidence: 99%
“…1 Synthesis of N 4 ,N 4 ,N 9 ,N 9 -Tetraethylquinolino[7,8-h]quinoline-4,9-diamine (26). Excess neat diethylamine (20 mL) was added to 17 (100 mg, 0.258 mmol) and heated under reflux for 48−72 h. Water (50 mL) was added, and the residue was extracted (27). Sodium sulfite (0.084 g, 6.667 mmol) and 16 (0.050 g, 0.167 mmol) in water (10 mL) was refluxed for 4 h. The solvent was removed, and the crude reaction mixture was dissolved in DMSO and filtered then precipitated with EtOAc to give 27 (0.093 g, 26%).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…The first is one of access. The synthesis of quinolinoquinoline 2 and its derivatives is not simple, and there has been a low supply of these compounds. , The second relates to coordination environment. The five-membered ring formed on coordination of phenanthroline to a metal 4 can accommodate a wide range of metals with little distortion to either the ligand or the metal.…”
Section: Introductionmentioning
confidence: 99%
“…It has long been recognized that the aza derivatives of carcinogenic polycyclic hydrocarbons can themselves act as carcinogens (Cook & Thomson 1945). More recently it has been shown that diaza derivatives are particularly pertinent in this context (Pai & Ranadive 1965;Buu-Hoi et a1 1967, 1968. To extend our studies of such polycyclic compounds (Bloomfield et a1 1986;Upton 1986Upton , 1992Tucker et a1 1993a, b), a series of diazabenzo[c]phenanthrenes has been prepared and screened, prompted by the isosteric relationship between benzo[c]phenanthrene 1 and its diaza analogue 2.…”
mentioning
confidence: 99%